PENGARUH RISIKO TERHADAP MINAT INVESTASI DENGAN PENGETAHUAN INVESTASI SEBAGAI MODERASI TERKAIT KASUS TRADING BINOMO DAN ROBOT TRADING : . - Ketut Tanti Kustina; I Gede Eka Sujaya Harta (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The public, particularly the younger generation, has recently become quite interested in the topic of investing in the capital market. Increased investment understanding must be weighed against the great interest in student investments. In relation to examples case of trading binomo and trading robots for undergraduate students , the goal of this study is to ascertain the impact of risk on investment interest using investing knowledge as a moderator. The study that follows employs quantitative methodologies and relies on secondary data from books, journals, and faculty or university records as well as primary data from surveys. Purposive sampling is a sampling method. The Slovin formula was used to calculate the sample size, and 100 responders were obtained. The following research data analysis method makes use of SPSS for Windows and is called moderated regression analysis (MRA). It follows that risk influences investing interest positively and significantly. The perception of risk on the investment interest of undergraduate students , can be moderated by investment knowledge. Keywords: Risk, Investment Interest, Investment Knowledge